Problem of taking drugs by the students of Lublin schools - Książek, Piotr; Dreher, Piotr; Dreher, Sylwia; Mojsym-Korybska, Sylwia; Goraj, Mariusz; Słowińska, Agata (Journal of Education, Health and Sport, 2019)
Abstract Introduction. The problem of drug use among young people is noticeable and has its basis not only in the individual problem, but also in the broader sense of acceptance of the peer group or the prevailing fashion. Aim. The aim of the study is to identify the level of consumption of psychoactive substances by pupils of Lublin schools and to indicate the socio-demographic components of behavior. Material and methods. The study was conducted on a random sample of 1444 students from 32 schools. A survey questionnaire was used as an anonymous questionnaire. Results. Men are more likely to be exposed to drug use. Taking into account the level of schools attended by the students, the largest group dealing with drugs are middle school students. Drugs are not foreign to primary school students. The atmosphere at home affects the consumption of drugs. The highest level of knowledge about the organization of helping people who have a problem with drugs is the high school students. Conclusions. The study of the problem of drug use by students from Lublin schools is a serious social problem.